CONSEQUENCES OF THE ISRAELI WARS IN THE MIDDLE EAST SINCE 2023 - Jankovic, Slobodan (National interest, 2025)
In this paper, the causes and, in particular, the consequences of the war efforts undertaken by the Jewish country in the period of approximately two years (October 2023-October 2025) in the Middle East are analyzed. The author highlighted the shortcomings of various theoretical frameworks in the IR discipline. In contrast, the Matteo Marconi variation of the Italian neoclassical geopolitical school, which emphasizes culture, history, and will, is crucial in influencing the aims of foreign policy. Therefore, that line of thought is suitable as an explanatory tool for the described behavior of a physically-geographically small state. The first two chapters are dedicated to explaining the history and religion as factors that shape Israeli foreign policy. In the following chapters, the history and geopolitical reasoning of the episodes of the unique war effort, aimed against Hezbollah, Syria, Hamas, and generally against Palestinians and Iran, are presented. The author concludes that consequences are multifaceted, referring to the distribution of power, modes of its dissemination, and theoretically highlighting the weakness of the concept of soft power in a changing world order. Israel managed to secure the reward for the series of war crimes, including the genocide, with Western support. This reveals the comprehensive breakdown of international law and the mechanisms of the post-Second World War order. Key words: Israel, Palestine, World Order, Iran, Middle East, Donald Trump, Netanyahu